1994
DOI: 10.1111/j.1365-3024.1994.tb00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 94‐kilodalton antigen on Leishmania promastigote forms and its specific recognition in human and canine visceral leishmaniasis

Abstract: We have analysed by immunoblotting sera from humans and dogs with visceral leishmaniasis, from the Old World as well as the New. When lysates of promastigotes are used as antigens, antibodies against a 94 kDa Leishmania component are detected, regardless of the age and geographical origin of the patient, the serum antibody titre as measured by indirect immunofluorescence, and the number of arcs in counterimmunoelectrophoresis. Low dilutions of sera from patients with Old and New World cutaneous leishmaniasis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…However, some investigators disagree as to the most specific and sensitive antigen bands recognized by sera of patients and animals with leishmaniasis. [6][7][8][9][10][11][12] Differences in the antigens used, promastigotes from the exponential or stationary growth phase, different degrees of antigen reduction as a consequence of different concentrations of SDS and 2-mercaptoethanol in the sample buffer, and separation of the soluble fractions of the antigen and the pellet are some of the factors that could influence the results. Moreover, the size of the slab gels and the concentration of polyacrylamide used, as well as different molecular weight markers, may introduce slight variations in the separation of the fractions and in the relative molecular weights calculated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some investigators disagree as to the most specific and sensitive antigen bands recognized by sera of patients and animals with leishmaniasis. [6][7][8][9][10][11][12] Differences in the antigens used, promastigotes from the exponential or stationary growth phase, different degrees of antigen reduction as a consequence of different concentrations of SDS and 2-mercaptoethanol in the sample buffer, and separation of the soluble fractions of the antigen and the pellet are some of the factors that could influence the results. Moreover, the size of the slab gels and the concentration of polyacrylamide used, as well as different molecular weight markers, may introduce slight variations in the separation of the fractions and in the relative molecular weights calculated.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies [6][7][8] reported different results concerning the pattern obtained in Western blot analysis of the specific humoral immunoresponse to L. infantum antigens during the active course of the disease and during therapy in human leishmaniasis. Limited studies have been performed on dogs, 7,[9][10][11][12] and little is known about the natural evolution of this immunoresponse during active or latent asymptomatic canine infection, or during regression of the disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among and parasite. Sera reacting with leishmanial immunocompetent subjects in India, such antigens of 230, 75, 66, 50, 42, 18, 14 and rK39-based dipsticks, speci cally designed 12 kDa (Hoerauf et al, 1992), 65-66, 42, for rapid diagnosis under eld conditions, 14 and 12-13 kDa (Bogdan et al, 1990), have proved to be both highly sensitive and 94 kDa (Rolland et al, 1994) or 14, 18, 21, highly speci c in the serodiagnosis of VL 23 and 31 kDa (Marty et al, 1995) may (Sundar et al, 1998 and post-kala-azar only come from cases of leishmaniasis. In dermal leishmaniasis (Salotra et al, 2001).…”
mentioning
confidence: 98%
“…One drawback of serological assays with whole parasites is the existence of cross-reactivity with other pathogens, including Trypanosoma cruzi, mycobacteria, malaria parasites, or amoebae, which are coendemic with Leishmania in many parts of the world (7,51). The performance of serodiagnostic assays could be improved by using purified or recombinant leishmanial antigens, such as gp63 (40,41,56), Hsp70 (30,48), p94 (53), gp70 and p72 (24), p32 (61), rK39 (2,11), r gene B protein (rGBP) (15,31), H2A and H2B (31,57,58,59), rLACK (31), and the promastigote surface antigen 2 (rPSA-2) (18,31,37), or synthetic peptides (14,48) and antigens from promastigote-conditioned media (33).…”
mentioning
confidence: 99%